The Influence of Consumer Focus, Operational Focus on Business Results of Cafe and Warkop Angkringan Owners in East Java: Pengaruh Fokus Konsumen, Fokus Operasi Terhadap Hasil Bisnis Pemilik Kafe dan Warkop Angkringan di Jawa Timur - Nugroho, Brilian; Sukmono, Rita Ambarwati (Indonesian Journal of Law and Economics Review, 2022)
The purpose of this study was to determine the effect of consumer focus, operations focus on business results on cafe owners and Angkringan Warkop owners in East Java. This research is a descriptive study using quantitative methods. Probability sampling technique to determine the population, and using accidential sampling for sampling. for the number of samples in this study took as many as 150 respondents to be the research sample. Then the validity test and reliability test will be carried out by using the Smart PLS method as a data processing application to conclude the proposed hypothesis and to answer the problem formulation. The results of this study, show results that can prove that Consumer Focus, Operations Focus has an effect on Business Results owners of Cafes and Warkop Angkringan in East Java.